2022
DOI: 10.3892/ijmm.2022.5160
|View full text |Cite
|
Sign up to set email alerts
|

Insights regarding mitochondrial DNA copy number alterations in human cancer (Review)

Abstract: Mitochondria are the critical organelles involved in various cellular functions. Mitochondrial biogenesis is activated by multiple cellular mechanisms which require a synchronous regulation between mitochondrial DNA (mtDNA) and nuclear DNA (nDNA). The mitochondrial DNA copy number (mtDNA-CN) is a proxy indicator for mitochondrial activity, and its alteration reflects mitochondrial biogenesis and function. Despite the precise mechanisms that modulate the amount and composition of mtDNA, which have not been full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 183 publications
0
7
0
Order By: Relevance
“… 20 Additionally, the evaluation of mtDNA content in multiple cancers has shown vast fluctuation, suggesting that mitochondrial copies are not particularly in stringent regulation. 21 , 22 Certainly, the amount of mtDNA copy number may vary depending on tissue types and is mostly present mostly in high-energy cells such as skeletal, cardiac muscles, and brain cells. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 20 Additionally, the evaluation of mtDNA content in multiple cancers has shown vast fluctuation, suggesting that mitochondrial copies are not particularly in stringent regulation. 21 , 22 Certainly, the amount of mtDNA copy number may vary depending on tissue types and is mostly present mostly in high-energy cells such as skeletal, cardiac muscles, and brain cells. 3 …”
Section: Discussionmentioning
confidence: 99%
“…By comparing proliferative and senescent cells, we obtained evidence for an increase in mtDNA copy number in senescent cells. A decrease in mtDNA copy number, or mtDNA depletion, is seen in many cancers ( Abd Radzak et al, 2022 ). Vice versa, it has been speculated that the accumulation of mtDNA in senescent cells may be a key factor in suppressing tumorigenesis or inflammatory responses ( Miwa et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2015) found that mtDNA_CN was positively correlated with mitochondrial mass and the respiratory capacity. Variation in mtDNA_CN has been associated with diverse pathologies, such as cardiomyopathy, diabetes and cancer (Kaaman et al ., 2007; Dillon et al ., 2012; Holmström et al ., 2012; Pirinen et al ., 2020; Abd Radzak et al ., 2022). This cellular trait is moderately heritable, with heritability estimates in humans of 0.33 to 0.65 (Xing et al ., 2008; López et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%